Labeled loans and human capital investments - Britta Augsburg; Bet Caeyers; Sara Giunti; Bansi Malde; Susanna Smets (Institute for Fiscal Studies (IFS), 2023)
Imperfect capital markets and commitment problems impede lumpy human capital investments. Labeled loans have been postulated as a potential solution to both constraints, but little is known about the role of the label in influencing investment choices in practice. We draw on a cluster randomized controlled trial in rural India to test predictions from a theoretical model, providing novel evidence that labeled microcredit is effective in influencing household borrowing and investment decisions and increasing take-up of a lumpy human capital investment, a toilet.
Keywords: O16; D14; G41; H24; I12; I38; 330; credit constraints; microcredit; labels; commitment device; fungibility; sanitation; subsidies